Simple thermal-electrical model of photovoltaic panels with cooler-integrated sun tracker - Ngo, Xuan Cuong; Huynh, Thi Thuy Linh; Nguyen, Dinh Hoa Cuong; Nguyen, Duy Thuan; Le, Vinh Thang; Nguyen, Thi Hong (Hue University Journal of Science: Natural Science, 2022)
This paper presents a simple thermal-electrical model of a photovoltaic panel with a cooler-integrated sun tracker. Based on the model and obtained weather data, we analyzed the improved overall efficiency in a year as well as the performance in each typical weather case for photovoltaic panels with fixed-tilt systems with a tilt angle equal to latitude, fixed-tilt systems with cooler, a single-axis sun tracker, and a cooler-integrated single-axis sun tracker. The results show that on a sunny summer day with few clouds, the performance of the photovoltaic panels with the proposed system improved and reached 32.76% compared with the fixed-tilt systems. On a sunny day with clouds in the wet, rainy season, because of the low air temperature and the high wind speed, the photovoltaic panel temperature was lower than the cooler’s initial set temperature; the performance of the photovoltaic panel with the proposed system improved by 12.55% compared with the fixed-tilt system. Simulation results show that, over one year, the overall efficiency of the proposed system markedly improved by 16.35, 13.03, and 3.68% compared with the photovoltaic panel with the fixed-tilt system, the cooler, and the single-axis sun tracker, respectively. The simulation results can serve as a premise for future experimental models.